Breaking the silence habit : a practical guide to uncomfortable conversations in the #MeToo workplace - Beaulieu, Sarah (Berrett-Koehler Publishers, 2020)
"Top consultant Sarah Beaulieu offers a five-part framework that enables employees to have difficult but necessary conversations about sexual harassment and violence and develop new, better ways of working together"--